Implementasi Pelayanan Pembuatan KTP Digital di Desa Kelong Kecamatan Bintan Pesisir - Marlina Marlina; Kustiawan Kustiawan; Khairi Rahmi (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
Population administration services at the village level often face various challenges, such as technological limitations, lack of outreach, and low digital literacy among the community. These conditions hinder the provision of fast and efficient services, particularly in the KTP (National Identity Card) issuance process. Therefore, innovation in services is needed, one of which is the implementation of digital KTPs. This study aims to analyze the implementation of digital KTP services in Kelong Village, Bintan Pesisir District, Bintan Regency. This service is part of the government's efforts to digitize population administration, which is expected to improve the efficiency and quality of public services at the village level. The approach used in this study is descriptive qualitative, with data collection techniques through in-depth interviews, observation, and documentation. The theory used for analysis is the policy implementation theory of Van Horn and Van Meter, which involves six main indicators. The results show that the digital KTP service in Kelong Village has been implemented since 2022 and provides convenience for the community, especially in terms of service speed and the friendly attitude of village officials. The community feels that obtaining their KTPs is faster than the previous manual procedure. Furthermore, village officials demonstrated a friendly and helpful attitude during the service process, enhancing the community's positive experience. However, this study also identified several challenges in implementing digital ID card services, such as a lack of public awareness regarding the procedures and benefits of digital ID cards. Limited technological devices and unstable internet connections also hampered smooth service delivery. Furthermore, low levels of digital literacy in the community made it difficult for some to access the service effectively.